[Sb7Se8Br2]3+ and [Sb13Se16Br2]5+ – Double and Quadruple Spiro Cubanes from Ionic Liquids1. Issue 19 (8th January 2014) - Ahmed, Ejaz; Breternitz, Joachim; Groh, Matthias F.; Isaeva, Anna; Ruck, Michael
Abstract: The reaction of antimony and selenium in the bromine‐rich Lewis acidic ionic liquid [BMIm]Br· 4.7AlBr3 (BMIm: 1‐butyl‐3‐methylimidazolium) in the presence of a small amount of NbCl5 at 160 °C yielded dark‐red crystals of [Sb7 Se8 Br2 ][AlX4 ]3 . For X = Cl0.15(1) Br0.85(1), the compound is isostructural to [Sb7 S8 Br2 ][AlCl4 ]3 [ P 21 21 21, a = 12.5132(5) Å, b = 17.7394(6) Å, c = 18.3013(6) Å]. For a higher chlorine content, X = Cl0.58(1) Br0.42(1), a slightly disordered variant with a bisected unit cell is found [ P 21 21 2, a = 12.3757(3) Å, b = 17.4116(5) Å, c = 9.0420(2) Å]. The [Sb7 Se8 Br2 ] 3+ heteropolycation ( C 2 symmetry) is a spiro double‐cubane with an antimony atom on the shared corner. From this distorted octahedrally coordinated central atom, tricoordinate selenium and antimony atoms alternate in the bonding sequence. The terminal antimony atoms each bind to a bromine atom. Quantum chemical calculations confirm polar covalent Sb–Se bonding within the cubes and indicate three‐center, four‐electron bonds for the six‐coordinate spiro atoms. The calculated charge distribution reflects the electron‐donor role of the antimony atoms. The use of a chlorine‐rich ionic liquid resulted in the formation of triclinic [Sb13 Se16 Br2 ][AlX4 ]5 with X = Cl0.80(1) Br0.20(1) [ P 1, a = 9.0842(5) Å, b = 19.607(1) Å, c = 21.511(1) Å, α = 64.116(6)°, β = 79.768(7)°, γ = 88.499(7)°]. The cationic cluster [Sb13 Se16 Br2 ] 5+ is a bromine‐terminated spiro quadruple‐cubane. This 31 atom concatenation of four cubes is assumed to be the largest known discrete main group polycation. A similar reaction in a chloride‐free system yielded [Sb7 Se8 Br2 ][Sb13 Se16 Br2 ][AlBr4 ]8 . In its monoclinic structure [ P 2/ c, a = 27.214(5) Å, b = 9.383(2) Å, c = 22.917(4) Å, β = 101.68(1)°], the two types of polycations alternate in layers along the a axis. In the series [Sb4+3 n Se4+4 n Br2 ] (2+ n )+, these cations are the members with n = 1 and 3. Abstract : Reactions under smooth conditions in ionic liquids facilitate the formation of the large heteronuclear main group polycations [Sb7 Se8 Br2 ] 3+ and [Sb13 Se16 Br2 ] 5+ .